FAM110A promotes mitotic spindle formation by linking microtubules with actin cytoskeleton - Aquino-Perez, Cecilia; Safaralizade, Mahira; Podhajecky, Roman; Wang, Hong; Lansky, Zdenek; Grosse, Robert; Macurek, Libor (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Precise segregation of chromosomes during mitosis requires assembly of a bipolar mitotic spindle followed by correct attachment of microtubules to the kinetochores. This highly spatiotemporally organized process is controlled by various mitotic kinases and molecular motors. We have recently shown that Casein Kinase 1 (CK1) promotes timely progression through mitosis by phosphorylating FAM110A leading to its enrichment at spindle poles. However, the mechanism by which FAM110A exerts its function in mitosis is unknown. Using structure prediction and a set of deletion mutants, we mapped here the interaction of the N- and C-terminal domains of FAM110A with actin and tubulin, respectively. Next, we found that the FAM110A-Δ40-61 mutant deficient in actin binding failed to rescue defects in chromosomal alignment caused by depletion of endogenous FAM110A. Depletion of FAM110A impaired assembly of F-actin in the proximity of spindle poles and was rescued by expression of the wild-type FAM110A, but not the FAM110A-Δ40-61 mutant. Purified FAM110A promoted binding of F-actin to microtubules as well as bundling of actin filaments in vitro. Finally, we found that the inhibition of CK1 impaired spindle actin formation and delayed progression through mitosis. We propose that CK1 and FAM110A promote timely progression through mitosis by mediating the interaction between spindle microtubules and filamentous actin to ensure proper mitotic spindle formation.
Keywords: kaseinkinasa I; mitosis; Humans; HeLa buňky; Actin Cytoskeleton; aparát dělícího vřeténka; Protein Binding; aktiny; mitotic spindle; mitóza; Microtubules; lidé; Casein Kinase I; Cell Cycle Proteins; mikrotubuly; protein kinase; HeLa Cells; Spindle Apparatus; vazba proteinů; proteiny buněčného cyklu; Mitosis; Actins; microtubules; actin; mikrofilamenta